Analysis of the Determinants of Participation, Strengths and Weaknesses of Vocational Trainings of Federally Administered Tribal Area's Development Authority - Sami Ullah; Zilakat K. Malik (International Journal of Economics and Financial Issues, 2020)
Modern economist emphasized human capital formation for socio-economic development. Human capital theory considered education and training essential tools for human capital formation. This study was conducted to analyze what factors determines participation rate of youth in vocational trainings of Federally Administered Tribal Area's Development Authority. Study also focused strengths and weaknesses of the trainings delivered. Data was collected on well-structured questioners from 400 respondents selected through disproportionate simple random sampling. The results revealed that age, marital status, father education, father profession, family size, family income and employment status before participation have significant effect on participation rate. Short duration, poor linkages with industries, lack of tool kits, career counseling, internship facility and post training financial support were recorded potential issues that challenged the achievement of anticipated outcomes of the program.